Utility based regional purchasing power parities - Martin Missong; Anja Rolf (Kiel University, Department of Food Economics and Consumption Studies, 2004)
Calculation of purchasing power parities based on observed consumer behaviour typically relies on the existence of some kind of 'international preferences'. We argue that this unrealistic assumption can be abandoned in 'regional' studies of purchasing power, where prices in both territories under study might differ only slightly. Drawing on recent results for the derivation of equivalence scales, we develop a model of regional purchasing power and discuss several procedures for testing model specification. The model is applied to data of the German Income and Expenditure Survey 1998 to estimate the wedge between purchasing power in the western and eastern part of Germany.
Keywords: C43; D12; F01; 330; Kaufkraftparität; Regionalforschung; Empirische Methode; Deutschland